Actual and preferred contraceptive sources among young people: findings from the British National Survey of Sexual Attitudes and Lifestyles. Issue 9 (26th September 2016) - Geary, Rebecca S; Tomes, Caroline; Jones, Kyle G; Glasier, Anna; Macdowall, Wendy; Datta, Jessica; Sonnenberg, Pam; Wellings, Kaye; French, Rebecca S; Mercer, Catherine H; Johnson, Anne M
Abstract : Objective: To describe actual and preferred contraceptive sources among young people in Britain and whether discordance between these is associated with markers of sexual risk behaviour or poor sexual health. Design: Cross-sectional probability sample survey. Setting: British general population. Participants: 3869 men and women aged 16–24 years interviewed for the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3) between 2010 and 2012. Main outcome measures: Reported source of contraceptive method(s) and preferred source if all were available and easily accessible. Results: Of the 75% of young people (aged 16–24) who were heterosexually active (1619 women, 1233 men), >86% reported obtaining contraceptives in the past year. Most common sources were general practice (women, 63%) and retail (men, 60%): using multiple sources was common (women 40%, men 45%). Healthcare sources were preferred by 81% of women and 57% of men. Overall, 32% of women and 39% of men had not used their preferred source. This discordance was most common among men who preferred general practice (69%) and women who preferred retail (52%). Likelihood of discordance was higher among women who usually used a less effective contraceptive method or had an abortion. It was less likely among men who usually used a less effective method of contraception and men who were not in a steady relationship. Conclusions: Most young people in Britain obtained contraception in the past year but one-third had not used their preferred source. Healthcare sources were preferred. Discordance was associated with using less effective contraception and abortion among young women. Meeting young people's preference for obtaining contraception from healthcare sources could improve uptake of effective contraception to reduce unwanted pregnancies.